2023
DOI: 10.1021/acsomega.3c01764
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insights into the Formation and Structure of S–N Containing Cyclic Peptides

Abstract: Cyclic peptides are known to have biologically important roles and may also be applicable to the pharmaceutical and other industries. Furthermore, thiols and amines, which are found throughout biological systems, can react to form S−N bonds and to date, ∼100 biomolecules containing such a bond have been identified. However, while there are in principle numerous S−N containing peptide-derived rings possible, only a few are presently known to occur in biochemical systems. Density functional theorybased calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Formation of 5-membered rings in a protein involving nucleophilic attack of a backbone nitrogen, while uncommon, has been experimentally observed such as 1,2-thiazolidin-3-one formation observed in Protein Tyrosine Phosphatase 1B. , Computationally, we have also shown that small ring cyclizations can be thermodynamically preferred . It is noted that we calculated the relative free energies of the corresponding 6- and 5-membered rings for Gln92 γS-Crystallin (Table S2).…”
Section: Resultsmentioning
confidence: 62%
“…Formation of 5-membered rings in a protein involving nucleophilic attack of a backbone nitrogen, while uncommon, has been experimentally observed such as 1,2-thiazolidin-3-one formation observed in Protein Tyrosine Phosphatase 1B. , Computationally, we have also shown that small ring cyclizations can be thermodynamically preferred . It is noted that we calculated the relative free energies of the corresponding 6- and 5-membered rings for Gln92 γS-Crystallin (Table S2).…”
Section: Resultsmentioning
confidence: 62%